Importance of Institutional Development for Western Balkan Countries - Milorad Filipovic (European Regional Science Association (ERSA), 2006)
Western Balkan countries comprises following entities: Bosnia and Hercegovina, Serbia and Montenegro, Kosovo and Metohija, Albania and Macedonia. Even there are just four sovereign(internationaly recognised) states among those entities, number of different names (8) shows to us all fragmentation and tendencies toward further dissolution of this region to increasing number of small and weak states. Tendencies that are shown in WB region are quite different from those in other transition countries in Europe. Instead of cooperation in economic, financial and all other important fields, like Visegrad group countries did in nineties and strenghten their negotiation position compared with the EU, WB countries try to flatter to EU member states and to build their better position through deterioration of the position of other regional states. On the internal plan, all WB countries are still rely on weak institutional capacity - mechanisms that enables governments non-transparent behavior, manipulation with judicial system and judges, selective implementation of the laws, very high and resistant level of corruption in all social and economic fields, surviving of organised crime structures which are very often related to government officials at all levels of authority etc. Integration of WB countries in the EU will be very long term and difficult process as the precondition for that will be building of effective institutional mechanisms that could provide governance comparative with other transition countries and in more distant future with European mature market economies. It isimportant also to establish efficient regional cooperation and to increase level of income and competitiveness to cope with the competition from EU. Experiences from other Balkan countires should be useful for WB region - Greek's as one old member state and Romania's and Bulgaria's as candidate meber states. WB countries expect to have greater understanding of EU officials for the very serious problems that have to be resolved and it is out of question that without important support from outside WB it will be impossible to do so.
Keywords: 330